2016
DOI: 10.1002/ls.1364
|View full text |Cite
|
Sign up to set email alerts
|

Static characteristics of ferrofluid finite journal bearing considering rotational viscosity effect

Abstract: Considering the rotation of ferromagnetic particles, the present study investigates hydrodynamic lubrication by ferrofluids of finite journal bearings using the Shliomis model. A magnetic field created by displaced finite wire is used. A numerical solution for the modified Reynolds equation using the finite difference method is obtained. Static characteristics of finite journal bearings are analysed using three control parameters: rotational viscosity, magnetization and volume concentration of the ferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The converging-diverging geometry of a journal bearing gives place to the rupture of the film (cavitation's phenomenon) in the divergent space when the pressure becomes less than atmospheric pressure. For us to resolve the Equation 13, the boundary conditions used are e p θ; e z ¼ 0:…”
Section: The Dimensionless Reynolds Equation Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The converging-diverging geometry of a journal bearing gives place to the rupture of the film (cavitation's phenomenon) in the divergent space when the pressure becomes less than atmospheric pressure. For us to resolve the Equation 13, the boundary conditions used are e p θ; e z ¼ 0:…”
Section: The Dimensionless Reynolds Equation Ismentioning
confidence: 99%
“…Taking into account the ferromagnetic particles rotation, Shliomis proposed a ferrofluid flow model. Using this model for different lubrication bearings, researchers found that Brownian motion of the lubricant together with rotation of the magnetic moments within the particles produces rotational viscosity, which supports more load.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, proper rotation of ferromagnetic particles within the carrier base fluid in the presence of magnetic fields affects the fluid viscosity and thus the journal bearing characteristics. Laghrabli et al [19,20] investigated the influence of ferromagnetic particles rotation on the static behavior of finite journal bearing operating with ferrofluids under the effect of a magnetic field generated by a finite wire. Using both Shliomis and Jenkins models, these authors calculated the journal bearing static characteristics and they confirmed that the use of magnetic fluids, compared to Newtonian ones, increases de pressure and consequently the load carrying capacity of the journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…This locally changes the effective viscosity, locally changing the resistance of the lubricant transportation. In addition, often these effects are accompanied by an attracting force between the fluid and the field, giving rise to an extra body force in the lubrication layer (Laghrabli et al, 2017a(Laghrabli et al, , 2017b. In general, it can be said that locally changing this rheological behaviour has similar effects as locally changing the geometry of the bearing van Ostayen, 2017a, 2017b).…”
Section: Introductionmentioning
confidence: 99%